(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
This paper investigate the effects of Hall currents on free-convective steady laminar boundary-layer flow, past a semi-infinite vertical plate, for large temperature differences . A uniform magnetic field is applied perpendicular to the plate. The fluid thermal conductivity is assumed to vary as a linear function of temperature. The fluid viscosity is assumed to vary as a reciprocal of a linear function of temperature. The usual Boussinesq approximation is neglected. The nonlinear boundary layer equations governing the problem under consideration are solved numerically by applying an efficient numerical technique based on the shooting method. The effects of the magnetic parameter M, the density / temperature parameter n, the thermal conductivity parameter S, the viscosity temperature are examined on the velocity and temperature distribution as well as the coefficient of heat flux and shearing stress at the plate .